ZEB1 expression is associated with prognosis of intrahepatic cholangiocarcinoma. Issue 7 (15th December 2015) - Terashita, Katsumi; Chuma, Makoto; Hatanaka, Yutaka; Hatanaka, Kanako; Mitsuhashi, Tomoko; Yokoo, Hideki; Ohmura, Takumi; Ishizu, Hiroyuki; Muraoka, Shunji; Nagasaka, Atsushi; Tsuji, Takahiro; Yamamoto, Yoshiya; et al.
Abstract : Background/Aim: Intrahepatic cholangiocarcinoma (ICC) is one of the most aggressive malignant tumours, so the identification of molecular targets for ICC is an important issue. Zinc finger E-box binding homeobox 1 (ZEB1) is a key inducer of epithelial–mesenchymal transition (EMT). The aim of the present study was to clarify the clinical significance of ZEB1 in ICC and the associations between ZEB1 expression and EMT-related proteins. Methods: We immunohistochemically examined the expression of EMT-related proteins, namely ZEB1, vimentin and E-cadherin, in ICC specimens from 102 patients. The clinicopathological and prognostic values of these markers were evaluated. Results: ZEB1 and vimentin were expressed in 46.1% and 43.1% of tumours, respectively, and E-cadherin expression was lost in 44.1% of tumours. ZEB1 expression showed a significant inverse correlation with E-cadherin expression (p=0.004) and a positive correlation with vimentin expression (p=0.022). Altered expression of ZEB1 was associated with aggressive tumour characteristics, including advanced tumour stage (p=0.037), undifferentiated-type histology (p=0.017), lymph node metastasis (p=0.024) and portal vein invasion (p=0.037). Moreover, overall survival rates were significantly lower for patients with high ZEB1 expression than for patients with low ZEB1 expression (p=0.027). Kaplan–Meier analysis also identified E-cadherin expression (p=0.041) and vimentin expression (p=0.049) as prognostic indicators for overall survival. Conclusions: ZEB1 expression is associated with tumour progression and poor prognosis in patients with ICC through positive correlations with vimentin and negative correlations with E-cadherin. ZEB1 expression is associated with a poor prognosis and might be an attractive target for the treatment of ICC.